ANTHROPOCENTRIC OR BIOCENTRIC? SOCIO-CULTURAL, ENVIRONMENTAL, AND POLITICAL DRIVERS OF URBAN WILDLIFE SIGNAGE PREFERENCES AND SUSTAINABLE COEXISTENCE - Itai Beeri (PEOPLE: International Journal of Social Sciences, 2025)
What determines whether the public favors anthropocentric or biocentric signage in urban contexts? As cities face the intensifying challenges of human–wildlife encounters in the Anthropocene, the need for policy responses grows urgent. This research positions signage preferences within the fields of public administration, local politics, environmental governance, and urban management, conceptualizing signage as a policy instrument that reflects broader socio-environmental and political dynamics. Unlike earlier studies that approach signage mainly as a behavioral nudge, we examine the socio-cultural, environmental, and political dimensions that influence attitudes along the anthropocentric–biocentric spectrum. While anthropocentric signage highlights human safety and casts wildlife as hazardous or problematic, biocentric signage underscores coexistence, ecological interdependence, and shared constraints. Using data from a large-scale public opinion survey, we analyze the case of wild boars and the related urban-environmental tensions in Mount Carmel and the municipality of Nesher. The findings reveal that socio-cultural vulnerability, perceptions of harm, support for policy, and political ideology all play a decisive role in shaping signage preferences. By doing so, the study contributes to scholarship on environmental governance, urban management, urban semiotics, and policy design, showing how signage functions as a contested political and ecological symbol. We conclude with a discussion of the implications for municipal governance, morality policies, and the aesthetics of urban signage.